An alternative evolutionary pathway for the twin‐tail goldfish via szl gene mutation. Issue 4 (27th June 2018) - Abe, Gembu; Lee, Shu‐Hua; Li, Ing‐Jia; Ota, Kinya G.
Abstract: The twin‐tail of ornamental goldfish provides unique evolutionary evidence that the highly conserved midline localization of axial skeleton components can be changed by artificial selection. This morphological change is known to be caused by a nonsense mutation in one of the recently duplicated chordin genes, which are key players in dorsal–ventral (DV) patterning. Since all of the multiple twin‐tail ornamental goldfish strains share the same mutation, it is reasonable to presume that this mutation occurred only once in domesticated goldfish. However, zebrafish with mutated szl gene (another DV patterning‐related gene) also exhibit twin‐tail morphology and higher viability than dino/chordin ‐mutant zebrafish. This observation raises the question of whether the szl gene mutation could also reproduce the twin‐tail morphology in goldfish. Here we show that goldfish have at least two subfunctionalized szl genes, designated szlA and szlB, and depletion of these genes in single‐fin goldfish was able to reproduce the bifurcated caudal fin found in twin‐tail ornamental goldfish. Interestingly, several phenotypes were observed in szlA ‐depleted fish, while low expressivity of the twin‐tail phenotype was observed in szlB ‐depleted goldfish. Thus, even though szl gene mutations may produce twin‐tail goldfish, these szl gene mutations might not be favorable for selection in domestic breeding. These results highlight the uniqueness and rarity of mutations that are able to cause large‐scale morphological changes, such as a bifurcated axial skeleton, with high viability and expressivity in natural and domesticated populations. GRAPHICAL ABSTRACT: Mutations in the chordin gene are invariably found in twin‐tail goldfish, but depletion of the szl gene is also able to reproduce the phenotype. Low phenotype penetrance and associated dysfunction may prevent selection of mutant szl in goldfish.